Cultural hybridity in central and southern Jordan at the end of the Pre-Pottery Neolithic A - Finlayson, B; Makarewicz, CA; Smith, SJ (CNRS Editions, 2024)
Our understanding of the transition from the PPNA to the PPNB in central and southern Jordan has undergone significant changes in recent decades. Initially, it appeared that the PPNB arrived in the region fully formed during the Middle PPNB, expressed at sites such as Beidha. Yet it retained features like circular architecture associated with the PPNA, and was thus presumed to indicate a time lag in its arrival from the north, where such structures had largely disappeared by the Middle PPNB. Fieldwork has uncovered a rich PPNA record in Jordan, but a marked cultural gulf between the PPNA and PPNB remains visible, for example visible in the contrast between pisé semi-subterranean PPNA architecture and the aboveground stone PPNB buildings, and in the appearance of naviform technology in PPNB chipped stone repertoires. Ongoing research has narrowed this gap, documenting a shift from semi-subterranean pisé constructions to circular free-standing stone structures during the Late PPNA, as well as the cessation of el-Khiam point manufacture and the emergence of an opposed platform blade technology that appears to echo parallel Early PPNB developments in chipped stone technology to the North. There is now no chronological gap between the Late PPNA and the Middle PPNB, and it appears that this central and southern Jordanian Late PPNA is an indigenous trajectory that developed into a local Middle PPNB while simultaneously adopting further external influences such as true naviform technology. However, recent work on the western edges of the Badia has identified a fully developed Early PPNB roughly contemporaneous with Late PPNA settlements in the adjacent wadi systems to the west. Out of sync with local developments, this Early PPNB presence suggests the arrival of a distinct group in the western Badia who maintained their identity, adding to the mix of local, already highly diverse, early Neolithic communities of central and southern Jordan. Interactions between these populations continued and through a process of cultural hybridisation formed the characteristic Middle and Late PPNB of the area.